Preemptive Propofol Administration in Spinal Cord Injury: Effects on Pain‐Induced Hypertension, Neuroinflammation, and Functional Recovery in Rats - Qun Cheng; Xiang‐Yu Fang; Rong‐En Qiu (Kaohsiung Journal of Medical Sciences)
ABSTRACT Spinal cord injury (SCI) triggers secondary damage, including pain‐induced hypertension, inflammation, and hemorrhage, impairing recovery. This study evaluated the efficacy of general anesthesia with preemptive propofol administration in mitigating secondary damage in SCI rats. SCI was induced in rats using a contusion model. Propofol (100 mg/kg) was administered intraperitoneally either 30 min before (preemptive) or 30 min after intermittent tail shock. Systolic blood pressure (SBP), body weight, food intake, inflammatory markers (interleukin‐1 beta [IL‐1β], interleukin‐6 [IL‐6]), hemorrhage markers, and serum levels of SCI biomarkers (glial fibrillary acidic protein [GFAP], myelin basic protein [MBP]) were measured. Functional recovery was assessed over 28 days using the Basso, Beattie, and Bresnahan (BBB) scale, horizontal ladder test, and rotarod test. Preemptive propofol administration effectively mitigated pain‐induced hypertension, enhanced body weight and food intake, and reduced inflammatory markers to levels comparable to unstimulated SCI rats. In contrast, propofol administered post‐stimulation was less effective. Preemptive administration significantly decreased GFAP levels and preserved MBP levels. Importantly, preemptive intervention reduced levels of hemoglobin and alpha hemoglobin, while post‐stimulation intervention showed no significant effect on hemorrhage. Behavioral assessments demonstrated improved locomotor recovery, motor coordination, and balance in preemptively treated rats compared to delayed or no intervention. Preemptive administration of propofol effectively reduces pain‐induced hypertension, inflammation, and gliosis while preserving myelin integrity and enhancing functional recovery in SCI rats. This intervention demonstrates significantly greater efficacy compared to delayed administration, underscoring the critical importance of timely treatment in mitigating secondary damage and improving outcomes after SCI.